Counseling about MP-ASI to Mothers for Improving Children's Nutritional Status - Maya Sari; Maimunah R; Nopitayanti Br Sitorus (PT Inovasi Pratama Internasional, 2022)
MP-ASI plays a role important in support Child growth . If mom not quick introduce MPASI with the right way for children moment he enter 6 months old , growing the flower can just disturbed . Activity MP-ASI socialization to mothers for Improving the Nutritional Status of Children carried out on day Tuesday, November 22, 2022 at the Village Office Dewi Sri District sea tador . Destination beginning MPASI socialization is for give understanding to women in the village area goddess sri that so important quality nutrition given to child ages 6-24 months as MPASI because in Century it's exclusive breastfeeding just no enough Fulfill nutrition child for grow and develop optimally. Reluctantly increasing knowledge moms regarding MPASI which is very important for the golden age child in grow and develop optimally. So will many mothers who will give solids in the right way, and follow existing rules like give eat appropriate time it means given when child already ready for eat, with sufficient nutrition from various menu options and types rich food carbohydrates , proteins and fats. And all his served in circumstances hygienic and processed by the mother yourself and given in a manner responsive .